FACTORS AFFECTING EPS ON NON-CYCLICALS CONSUMER SECTOR COMPANIES LISTED ON THE IDX - Herman, Veronica; Sufiyati , Sufiyati (International Journal of Application on Economics and Business, 2023)
The purpose of this study was to analyze the effect of Debt to Equity Ratio (DER), Return On Equity (ROE), Current Ratio, Firm Size and Total Assets Turnover (TATO) on Earning Per Share (EPS). The research sample consists of 93 non-cyclical consumer sector company data that have been listed on the Indonesia Stock Exchange for the 2018-2020 period. Data processing in this study used the EViews version 12 program with a purposive sampling technique. The results of this study prove that ROE and Firm Size have a positive and significant effect on EPS while DER, Current Ratio, and TATO have an insignificant effect on EPS.